Colheita semimecanizada de eucalipto em áreas declivosas - Brinate, Igor Batista (2016)
Worldwide, there is a growing demand of wood, which leads to an increase in planted areas. The mechanization has maximized the performance of forestry activities, but not all areas are liable to mechanization. The high slope of the land makes the machine traffic in the stands impossible, forcing producers to adopt manual methods and semi-mechanized methods. The aim of this study was to analyze, technically, two semi-mechanized forest harvesting techniques in hilly areas. Specifically, technically analyzes up to semi-mechanizes harvesting sloping areas extracted by manual tipping (traditional techniqye) and dragger winch (dragger winch’s technique), under conditions of high slope, without relief variation, called normal condition, and in areas with concave relief (caves), called critical areas. It was accomplished a time and motion study, calculating the productivity, operational efficiency and mechanical availability. The study of the traditional technique was carried out in the operational areas of forest harvesting belonging to farmers in partnership with a forestry company, located in the mountain central and south region of the state of Espírito Santo, while the study of dragger winch’s technique was conducted on a leased farm by the same company, belonging to the Paraíba Valley region, in the state of São Paulo. Four teams were evaluated in the traditional technique and six teams in dragger winch’s technique. The results for the operational steps were compared by the Student’s t test at 5 % probability. According to the time and motion study results, the extraction activity is the most uptime demand, and, because of the complexity of the critical areas, they stand out demanding more time than in normal conditions. The yield obtained in cutting at dragger winch’s technique stands out for being less stressful and more productive with 55.48 m³.HE-1 in normal condition and 49.53 m³.HE-1 in critical areas, compared to 10.12 m³.HE-1 and 5.48 m³.HE-1 in traditional technique. The manual tipping under normal conditions stood out presenting better productivity, with 6.88 m³.HE-1 , and the worst productivity in critical areas, with 1.2 m³. HE-1 . Yields of dragging obtained soft variation in productivity between the conditions, with 1.98 m³. HE-1 in normal condition and 2.28 m³.HE-1 in critical areas.The mechanical availability showed lower values in critical areas (84.17 %) due to increased wear of equipment. It follows that under normal conditions it is more feasible to use the semi-mechanized cutting extracted by manual overturning (traditional technique), but in terms of critical areas and roadless areas on the bottom, the semi-mechanized cutting extracted by winch (dragger winch) is the most qualified.